Social representations of comfort for patients' family members in palliative care in intensive care - Odisséia Fátima Perão; Eliane Regina Pereira do Nascimento; Maria Itayra Coelho de Souza Padilha; Daniele Delacanal Lazzari; Patrícia Madalena Vieira Hermida; Mayara Ana da Cunha Kersten (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To know the social representations of comfort for patients' family members in palliative care in intensive care. Method: Descriptive, qualitative study, theoretical framework adopted was Social Representations. 30 family members of patients admitted to an intensive care unit in palliative care participated. Data were collected through semi-structured individual interviews, organized and analyzed using the Collective Subject Discourse technique. Results: Pointed out as central ideas, positive and negative feelings of family members, communication and interaction with the team, ICU as excellence and palliative care as a measure of comfort for the patient and the family. Conclusion: The social representations about the comfort of family members of hospitalized patients in an intensive care unit in palliative care are identified by the family members' feelings during the visit, communication, and the humanized care applied by nursing professionals in the patients in palliative care.